PENGARUH MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI DI PT. MTI - Ahmad Fadhlan; Agung Surya Dwianto (Jurnal Bina Bangsa Ekonomika, 2024)
The aim of this research is to analyze and determine the influence of work motivation and work discipline partially and simultaneously on employee performance. This research uses a quantitative approach with the research subjects are employees of PT. MTI at the Merchant Operations section with a sample size of 45 respondents. This research uses data collection techniques through distributing questionnaires and supported secondary data. The data analysis method used is multiple linear regression analysis with data processing using the SPSS 27 program. The results of the research show that the work motivation variable does not have a partial or simultaneous effect on performance with a significance of 0.388, while the work discipline variable has a partial and simultaneous effect on PT.MTI employees performance with a significance of 0.001. With the Adjusted R Square value of the coefficient of determination (R²) is 18.6%.